(untitled) (SCIÉNDO INGENIUM, 2021)
The influence of the revocation of the suspended sentence for non-payment of civil compensation as a rule of conduct was investigated on the convicted person, his family and the State. To verify the research hypothesis, a sample made up of resolutions of revocation of the suspended sentence issued, in 2018 and 2019, by the Trujillo Preparatory Investigation Judges was chosen; the Executive Report on the Support of the 2019 Budget, of the Justice and Human Rights Sector; the report on the penitentiary population (POPE) and penitentiary establishments 2017 -2018; and, as a complement, a survey of 100 lawyers in criminal matters from Trujillo regarding the subject of study, in addition, the legal provisions issued in 2020 were analyzed. To collect data, the techniques of documentary analysis and the survey were used, which were organized and processed statistically, to later be presented in tables and statistical figures, for discussion with the general and particular methods of science. It was concluded that: the revocation of the revocation of the suspended sentence for non-compliance with the payment of civil damages as a rule of conduct, has a direct positive influence on the sentenced person, and indirectly on his family and the State.